Open innovation’s effects on Indonesia’s digital health market and related societal issues - Irianna Futri; Phaninee Naruetharadhol (Cogent Arts & Humanities, 2025)
Indonesia’s rapid digitalization, particularly in the healthcare sector, has been significantly impacted by the ongoing COVID-19 pandemic. This study aims to analyze the impact of open innovation in the digital healthcare market in Indonesia, a developing country with a population of over 273 million. The research method used is qualitative descriptive and combines SWOT analysis by utilizing secondary data from literature, industry reports, policy documents and related statistics. This study identifies various opportunities and challenges faced by the digital healthcare sector, including the role of the government in supporting the digitalization of healthcare services. The findings show that open innovation can improve access to healthcare services, especially in remote areas, by implementing telemedicine and health applications. However, infrastructure, regulation and digital literacy challenges remain as significant barriers. This study is expected to provide valuable insights for stakeholders in formulating strategies to develop the digital healthcare sector in Indonesia and encourage a collaboration between the government, private sector and communities in creating a more inclusive and sustainable healthcare ecosystem.